Neurointerventional techniques : tricks of the trade - Gonzalez, L. Fernando, 1969-; Albuquerque, Felipe C.; McDougall, Cameron G. (New York : Thieme, 2015)
"Neurointerventional surgery is a practical reference that includes core procedures used in the growing neurointerventional subspecialty. The step-by-step, concise presentation of procedures along with original line drawings and high-quality images concisely distill a wealth of information, making it easy for both novice and expert neurointerventionists to review how procedures are performed. The book includes over 50 specific procedures as well as important chapters on access points, physiological testing, and pharmacology in the endovascular suite"--Provided by publisher.
Includes bibliographical references and index.
English
Keywords: Endovascular Procedures -- methods; Neurosurgical Procedures -- methods